A scale for measuring the applicability of lean practices in IT support services. Issue 5 (2014) - Goutam Kumar Kundu; Jayachandra Bairi
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to present research that was conducted with an objective to conceptualize and develop an instrument for the measurement of the perception of IT support service practitioners about the applicability of lean concepts in IT support services. Design/methodology/approach – Scale items were identified from current literature and the survey instrument was used to collect data from IT support service practitioners. The constructs' measurement models were tested and the scale was validated by using statistical tools. Findings – The results of the study indicate that the operational measures developed here satisfy the criteria for unidimensionality, reliability and validity. Research limitations/implications – While selecting and excluding measurement items for the survey, the researchers have followed established principles of survey research; but it may have been affected by the personal bias of the author. The sample for the survey was drawn from IT support service companies located in India, thus the results are generalizable only to the extent that these businesses represent the population of all businesses. Another limitation is that no prior survey/case studies were carried out to collect IT service practitioner's perception about the applicability of lean practices. Originality/value – This paper provides a new measurement instrument for measuring the applicability of lean practices in IT support service environment.